Implementasi metode inkuiri dalam meningkatkan keterampilan sains siswa kelas V pada materi membuat magnet di SD Inpres Pannujuang, Sulawesi Selatan - Magfirah Magfirah; Daroe Iswatiningsih (Universitas Sebelas Maret, 2025)
This study aims to describe the implementation of the inquiry method in teaching Social Science (IPAS) on the topic of making magnets and to analyze its impact on the science process skills of fifth-grade students at SD Inpres Pannujuang, South Sulawesi. The study addresses students’ low understanding of magnetic force concepts and their practical applications. A qualitative descriptive approach was employed, with data collected through observation, interviews, and documentation, and analyzed using Miles and Huberman’s interactive model. The results show that the inquiry method, implemented through orientation, problem formulation, hypothesis formulation, data collection, data analysis, and conclusion stages, effectively improved students’ science process skills, including observing, questioning, experimenting, and drawing evidence-based conclusions. The method also enhanced students’ curiosity, activeness, collaboration, and scientific communication. In conclusion, the inquiry method is effective in fostering science process skills and scientific literacy in primary school students. It is recommended to apply this method to other IPAS topics requiring investigative learning.